2011
DOI: 10.1037/a0022598
|View full text |Cite
|
Sign up to set email alerts
|

Moral anger, but not moral disgust, responds to intentionality.

Abstract: We propose that, when people judge moral situations, anger responds to the contextual cues of harm and intentionality. On the other hand, disgust responds uniquely to whether or not a bodily norm violation has occurred; its apparent response to harm and intent is entirely explained by the coactivation of anger. We manipulated intent, harm, and bodily norm violation (eating human flesh) within a vignette describing a scientific experiment. Participants then rated their anger, disgust, and moral judgment, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
153
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 170 publications
(173 citation statements)
references
References 22 publications
13
153
1
1
Order By: Relevance
“…In the social domain, however, disgust may also respond categorically to a particular class of violations-those pertaining to bodily-purity norms, or the rules governing the proper uses of the body within a given culture (see Haidt, Rozin, McCauley, & Imada, 1997;Horberg, Oveis, Keltner, & Cohen, 2009;Rozin et al, 1999;Russell & Giner-Sorolla, 2011a, in press). Consistent with this thesis, Russell and Giner-Sorolla (2011a) found that, in direct contrast to anger, levels of reported disgust were unaffected by whether or not an act of wrongdoing was performed intentionally, and affected only by whether the act violated a bodily norm.…”
Section: Anger Disgust and Moral Judgmentsupporting
confidence: 62%
See 1 more Smart Citation
“…In the social domain, however, disgust may also respond categorically to a particular class of violations-those pertaining to bodily-purity norms, or the rules governing the proper uses of the body within a given culture (see Haidt, Rozin, McCauley, & Imada, 1997;Horberg, Oveis, Keltner, & Cohen, 2009;Rozin et al, 1999;Russell & Giner-Sorolla, 2011a, in press). Consistent with this thesis, Russell and Giner-Sorolla (2011a) found that, in direct contrast to anger, levels of reported disgust were unaffected by whether or not an act of wrongdoing was performed intentionally, and affected only by whether the act violated a bodily norm.…”
Section: Anger Disgust and Moral Judgmentsupporting
confidence: 62%
“…For example, anger provoked in one situation has been shown to "spill over" into orthogonal decisions about blame and punishment, but dissipate when relevant cues of justice are highlighted (see Goldberg et al, 1999). At least three antecedent features of a harmful event seem to impact upon the intensity of anger: severity (Rule & Duker, 1973;Schwartz, Kane, Joseph, Running head: MORAL EMOTIONS AND MITIGATING CIRCUMSTANCES 5 & Tedeschi, 1978), intentionality (Russell & Giner-Sorolla, 2011a), and justifiability (Hewitt, 1975;Quigley & Tedeschi, 1996). Additionally, whether or not the act of harm was perceived to be avoidable or controllable may be a fourth antecedent, though findings for this dimension are less consistent (cf.…”
Section: Anger Disgust and Moral Judgmentmentioning
confidence: 99%
“…To conclude, although there is sufficient evidence to believe that disgust and anger are connected in their response to moral judgments that include pure transgressions; they, in fact, act distinctively (Chapman & Anderson, 2013). One potential explanation could be that disgust is considered an avoidance-motivated and distancing emotion; whereas anger is considered more of an approach-motivated and reactive emotion (Mackie, Devos, & Smith, 2000;Russell & Giner-Sorolla, 2011a;Ugazio et al, 2012). However, this assumption needs to be tested empirically in order to be confirmed.…”
Section: Claim 3: Disgust Is Just Anger In Disguisementioning
confidence: 97%
“…Once again I am also concerned with how much of this claim is connected to moral evaluations of pure transgressions or those reminding us of physical disgust. For instance, there is evidence suggesting that anger and not disgust responds more powerfully to manipulations of the intentionality of a wrong action and whether it causes harm to others (Giner-Sorolla, Bosson, Caswell, & Hettinger, 2012;Gutierrez & Giner-Sorolla, 2007;Russell & Giner-Sorolla, 2011a).…”
Section: Claim 3: Disgust Is Just Anger In Disguisementioning
confidence: 99%
See 1 more Smart Citation